THE EFFECT OF LIQUIDITY, LEVERAGE, PROFITABILITY, INDEPENDENT COMMISSIONERS, AND INSTITUTIONAL OWNERSHIP ON DIVIDEND POLICY WITH FREE CASH FLOW AS A MODERATING VARIABLE IN MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE PERIOD OF - Frisky Anistya; Fahmi Natigor Nasution; Keulana Erwin (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze whether liquidity, leverage, profitability, independent commissioner, and institutional ownership affect dividend policy with free cash flow as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The study employed purposive sampling, selecting 25 companies from a population of 47 mining sector firms listed on the IDX, yielding 100 observations. Hypothesis testing was conducted using panel data regression analysis and Moderated Regression Analysis (MRA) with EViews software. The results indicate that liquidity does not affect dividend policy. Leverage does not affect dividend policy. Profitability has a significant positive effect on dividend policy. Independent commissioner and institutional ownership do not affect dividend policy. Free cash flow cannot moderate the effect of leverage, profitability, or institutional ownership on dividend policy.